Trauma care pre-hospital manual - Greaves, Ian; Porter, Keith M. (CRC Press, 2019)
This new book provides evidence based guidelines for the immediate clinical management of major trauma. It has been written by clinicians with many years of trauma experience, and endorsed as authoritative by Trauma Care (UK)The UK now has highly effective trauma systems. Clinical developments include the introduction of damage control resuscitation, tranexamic acid, blood product resuscitation, novel hybrid resuscitation and an emphasis on the control of major external haemorrhage as part of a new ABCDE approach. Consequently, more individuals with major trauma are surviving than ever before. Optimal pre-hospital care is essential for improved survival rates and reduced morbidity.